Analysis of Factors Leveraging Sustainability of Community-Based Drinking Water Supply (Case Study of Drinking Water Supply for The Pamsimas Program, Kapongan Sub-District, Situbondo Regency) - Nur Andriyanto; Asep Suheri; Prabawa Eka Soesanta (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
This research aims to identify the sustainability driving factors of drinking water provision in the PAMSIMAS program in Kapongan Sub-District, Situbondo Regency, focusing on community participation based on environmental, social, economic, technological, and institutional dimensions. This study utilizes a quantitative approach with the Rap-SPAM analysis method, a modification of Rapfish. The data used consist of both primary and secondary sources. Primary data are obtained through surveys, observations, and interviews with respondents, utilizing questionnaires. Secondary data is gathered through relevant literature reviews and various related institutions. The results of the Rap-SPAM simulation on 5 dimensions of sustainability, obtained 18 sensitive attributes or main leveraging factors. The main leverage attributes in the environmental dimension are the surrounding land condition, pollution potential, rainfall & rainy days, and quantity of raw water. In the social dimension, the main leverage attributes are community meetings, practices of using the water supply system, and community trust. In the economic dimension, the main leverage attributes are existence of fees for the development of the water supply system network, availability of funds for the development of the water supply system, existence of user fees, and affordability of user fees. In the technological dimension, the main leverage attributes are water efficiency of water use, ease of technology application, network leakages, and quality of received water. In the institutional dimension, the main leverage attributes are clear organizational structure, performance and financial reporting by the management to the users of the water supply system, and regulations for water supply management.